Biscuit Purchasing Procedure at PT. Semestanustra Distrindo Branch Banjarmasin - Boy sapto suryo; Hikmah Ariani (Economy Deposit Journal (E-DJ), 2022)
The research, entitled Biscuit Purchasing Procedure at PT. Semestanustra Distrindo in Banjarmasin aims to obtain an overview of "Biscuit Purchasing Procedure at PT. Semestanustra Distrindo Branch Banjarmasin. This type of research used in this final project is descriptive qualitative research, where the data obtained from the results of observations, interviews, documentation are then described qualitatively. The result of research on Indirect Biscuit Purchasing Procedure at PT. Semestanustra Distrindo Banjarmasin Branch shows that there are eight channels or stages, namely; Request salesmen or buyers, Conduct market surveys, Make a list of items to be purchased. Send a Purcashing Order, Receiving goods, Checking the goods that have been received, Returns, Paying transactions according to invoice procedures. After analyzing and discussing the indirect biscuit purchasing procedure at PT. Semestanustra Distrindo Banjarmasin Branch, the authors concluded that the indirect purchasing procedure at PT. Semestanustra Distrindo Banjarmasin Branch has been structured regularly and well, but the implementation is not optimal, the number of stages is carried out according to company needs. In order for procedures that are well structured and easy to implement, it is necessary to have regular training and outreach to employees and a flowcart.